The Use of Engineered Plant Viruses in a Trans-Kingdom Silencing Strategy Against Their Insect Vectors - Kolliopoulou, Anna; Kontogiannatos, Dimitrios; Swevers, Luc (Frontiers in Plant Science, 2020)
Plants, plant viruses, and their vectors are co-evolving actors that co-exist and interact in nature. Insects are the most important vectors of plant viruses, serving as both carriers and hosts for the virus. This trans-kingdom interaction can be harnessed for the production of recombinant plant viruses designed to target insect genes via the RNAi machinery. The selection of the adequate viruses is important since they must infect and preferentially replicate in both the host plant and the insect vector. The routes of transmission that determine the extent of the infection inside the insect vary among different plant viruses. In the context of the proposed strategy, plant viruses that are capable of transversing the insect gut-hemocoel barrier and replicating in insect tissues are attractive candidates. Thus the transmission of such viruses in a persistent and propagative manner is considered as a prerequisite for this strategy to be feasible, a characteristic that is found in viruses from the families Bunyaviridae, Reoviridae and Rhabdoviridae. In addition, several RNA viruses are known that replicate in both plant and insect tissues via a yet unclarified transmission route. In this review advances in knowledge of trans-kingdom transmission of plant viruses and future perspectives for their engineering as silencing vectors are thoroughly discussed.